2003
DOI: 10.1002/pen.10007
|View full text |Cite
|
Sign up to set email alerts
|

A study of the stick‐slip phenomenon in single‐screw extrusion of linear polyethylene

Abstract: We present results of a study on the stick‐slip phenomenon observed for two linear polyethylenes (HDPE and LLDPE). Experiments were carried out in a single screw extruder using dies of different diameters and L/D ratios. The pressure and the mass flow rate have been measured simultaneously and the instant mass flow rate was determined using laser Doppler velocimetry. Our results clearly confirm the hypothesis that the flow jumps from one stable branch to the other during oscillations as suggested in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Therefore, the volumes and the masses of the oscillating melt are very different and a dependence of the oscillation frequency on the size of the reservoir is evident. This influence of the reservoir volume (linked to the compressibility of the polymer) has been clearly established in the case of oscillating defect (stick-slip) for linear polymers [29,30].…”
Section: Periodical Destabilization Of the Upstream Flow Fieldmentioning
confidence: 95%
“…Therefore, the volumes and the masses of the oscillating melt are very different and a dependence of the oscillation frequency on the size of the reservoir is evident. This influence of the reservoir volume (linked to the compressibility of the polymer) has been clearly established in the case of oscillating defect (stick-slip) for linear polymers [29,30].…”
Section: Periodical Destabilization Of the Upstream Flow Fieldmentioning
confidence: 95%
“…The stick-slip defect is well known for linear polymers [1][2][3][4][5][6]: when imposing the flow rate on a capillary rheometer, one observes that above a critical value (corresponding to a critical shear ratė c or a critical shear stress *), the flow becomes unstable and gives rise to pressure oscillations in the reservoir and flow rate oscillations at the die exit. On the extrudate, this defect is characterized by a regular and periodic succession of zones of different aspects, generally sharkskined and smooth (Fig.…”
Section: General Presentation Of the Stick-slip Defectmentioning
confidence: 99%
“…Copyright 1996, The Society of Rheology) (t 1 ) and the pressure decrease (t 2 ) phases (Durand, 1993). All authors found that the compressible volume is more important than the volume of the reservoir (Durand, 1993;Kay et al, 2003). However, this result has never received until now a satisfactory interpretation (Cogswell, 1999).…”
Section: Description Of the Observed Phenomenamentioning
confidence: 91%
“…Figure 15 shows an example of this flow curve for a high density polyethylene (Kay et al, 2003). When working at imposed flow rate, its progressive increase allows to move along branch I, where may appear the sharkskin defect mentioned above.…”
Section: Description Of the Observed Phenomenamentioning
confidence: 93%